Strategi Kepala Madrasah dalam Meningkatkan Profesionalisme Guru - Teuku Alvinnur; Buhori Muslim; Fazlurrahman; Rahmat Raji (Jumper: Journal of Educational Multidisciplinary Research, 2026)
This study aims to analyze the principal strategies, obstacles, and challenges in improving the professionalism of teachers at MAS Baitul A’idah Bireuen. The study employed a qualitative descriptive approach. Data were collected through in-depth interviews, observations, and documentation involving the principal and teachers as key informants. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings reveal that the principal has implemented comprehensive strategies, including teacher professional development through training, workshops, In-House Training (IHT), academic and managerial supervision, strengthening an Islamic work culture, providing motivation and rewards, and competency-based teacher management. However, the implementation of these strategies is constrained by limited financial resources, differences in teacher competencies, varying levels of motivation, heavy administrative workloads, and limited access to professional development. Furthermore, the principal faces challenges related to digital transformation, changes in educational policies, increasing demands for educational quality, and the need to strengthen collaboration with stakeholders. The study concludes that improving teacher professionalism requires visionary, adaptive, innovative, and collaborative leadership to create sustainable professional development and improve the quality of Islamic education.